Skrining Dini Penyakit Paru-Paru Dengan Pemeriksaan Spirometri Pada Masyarakat - Tri Wahyuni; Taslim Taslim; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi; Nurhaedah Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Lung disease is a leading cause of morbidity and mortality in the community, particularly chronic obstructive pulmonary disease (COPD), asthma, and lung disorders caused by exposure to air pollution and smoking. Most lung diseases develop slowly and often go undetected in the early stages because symptoms are still mild. Early screening through spirometry is a simple, non-invasive, and effective method for detecting impaired lung function early. This Community Service activity aims to conduct early screening for lung disease through spirometry and raise public awareness of the importance of lung health. Implementation methods include lung health education, spirometry examinations, interpretation of results, and health counseling. The activity results showed the detection of impaired lung function in some participants and increased public knowledge and awareness about early detection of lung disease. Spirometry screening is expected to be a preventive measure in reducing the burden of lung disease in the community.